Global development finance : the development potential of surging capital flows, 2006. - World Bank. (Washington, DC : World Bank, 2006)
This volume provides analysis of key trends and prospects, including coverage of capital originating from developing countries themselves. Many low-income countries still have little or no access to international private capital, and instead depend largely on official finance from bilateral and multilateral creditors to support their development objectives. Capital flows are changing due to financial integration among developing countries, financial innovations, domestic debt markets, and the global role of the Euro. Net official flows continue to decline as official lending falls and there is more aid and debt relief for the poorest countries. To ensure economic stability, developing countries must manage capital flows with effective macroeconomic policies, prudent accumulation of reserves, careful management of oil-export revenues, and improvements in standards for the corporate sector.
v. 1. Review, analysis and outlook -- v. 2. Summary and country tables.
Includes bibliographical references.
lje 6/9/13
Loan
Keywords: Capital movements -- Developing countries; Debts, External -- Developing countries; International finance; Finance -- Developing countries; Investments, Foreign -- Developing countries; Economic development